Adverse drug reactions and cost effectiveness of non-steroidal anti-inflammatory drugs, muscle relaxants, and neurotropic drugs in patients with low back pain - Patel, I. B.; Bairy, K. L.; Bhat, S. N.; Shetty, D. J.; Chogtu, B.; Esha, R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective was to evaluate the adverse drug reactions (ADRs) and cost effectiveness of different classes of drugs in therapy of low back pain. Methods: A prospective observational study was carried out over a period of 12 months (November 2012 to November 2013) in which a total of 300 patients with low back pain were enrolled and divided equally into three groups – Group 1 (non-steroidal anti-inflammatory drugs [NSAIDs]), Group 2 (NSAIDs ± muscle relaxant), and Group 3 (NSAIDs ± muscle relaxant ± neurotropic drugs). Any ADR developed after the initiation of treatment at 3 weeks and 6 weeks was noted. Prescription cost per day was also calculated. Results: There was a male predominance in the study population with a mean age of 39.76±9.40 years. A total of 262 ADRs were noted among which most were seen in Group 3 (119 ADRs). Gastritis was the most common ADR in Group 1. Drowsiness was the most common ADR in Group 2 (30%) and 3 (46%). Prescription cost per day was highest in Group 3 (30.28±11.24 Indian Rupee [INR]) followed by Group 2 (25.92±8.66 INR) and Group 1 (12.22±3.38 INR). Conclusion: Patient on combination of three drugs (NSAIDs, muscle relaxants, and neurotropic agents) had maximum ADRs and their prescription cost per day was highest among the three groups.